Gamification in a Virtual Ecology (GIVE): Enhancing Classroom Engagement in Physical Education among Senior High School Students - Marcaida, John Louise M.; Ortega, Hans Christian A.; Castañeda, Edzel S.; Cadeliña, Pamela Mae M.; Garcia, Rolan Randolf I.; Valenzuela, Luwy R.; Tolentino, Julius Ceazar (Future Science / FSH-PH Publications, 2022)
The study was geared toward determining the influence of integrating Gamification in a Virtual Ecology (GIVE) in enhancing classroom engagement in physical education among senior high school students in a state university in Pampanga, Philippines. This qualitative-descriptive study included a complete enumeration of the Grade 12 Technical-Vocational-Livelihood (TVL) students who voluntarily participated in this qualitative investigation (n = 58) by responding to open-ended questions. Results of the open-ended questionnaire decipher the influence of gamification on students’ level of engagement and the barriers encountered upon its inclusion. The study utilized Braun and Clarke's Thematic Analysis strategy, which was aided by computer-assisted qualitative analysis software, MAXQDA Analytics Pro 2022. The study revealed two emerging themes that described the influence of gamification in the students' virtual ecology, namely: (1) the effects of the integration of gamified instruction on students’ engagement; and (2) students' problems in using gamified instruction. The findings of this study may predate the institutionalization of the prospective enhancement of the teacher’s capabilities through the aid of gamification to improve the classroom engagement of the students in a virtual ecology towards a better understanding of the lessons in physical education settings.